(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Surveillance of device-associated infections (DAIs) in intensive-care units (ICUs) is essential for a suitable healthcare strategy-planning. This study was conducted to determine the DAIs rate, microbial epidemiology, and antimicrobial resistance pattern (AMR) in ICU. Three major DAIs, ventilator associated pneumonia (VAP), catheter-associated urinary tract infection (CAUTI), and central line-associated bloodstream infection (CLABSI) were assessed prospectively during 6 months (2018 March 21 to September 22) in an 18-bed ICU of a tertiary teaching hospital in Tehran according to new CDC/NHSN definitions for surveillance of DAIs. The incidence of VAP, CAUTI, and CLABSI were 38.2, 8.9, and 13.5 per 1000 device-days respectively. The most organisms were Acinetobacter baumannii (34.9%), Klebsiella pneumonia (19%), E.coli (10.7%), Candida (10.7%), Enterococcus Spp. (8.7%), Pseudomonas aeruginosa (8.7%), and Staphylococcus aureus (2.9%). Klebsiella pneumoniae carbapenemase (KPC)-producing was 47.4%. Acinetobacter resistance to Ampicillin-sulbactam and carbapenems was 80.6% and more than 90% respectively. Methicillin resistant Staphylococcus aureus (MRSA) was 66.6% and Vancomycin-resistant Enterococcus (VRE) was 88.9%. This study showed high incidence of DAIs and resistant organisms in the ICU. Preventive measures are essential to decrease the rates.